Stress-Strain Behavior of Confined Class C Fly Ash-Based Geopolymer Concrete - Ummah, Galih Syifa’ul; Piscesa, Bambang; Tajunnisa, Yuyun (IPTEK The Journal of Engineering, 2024)
Fly ash-based geopolymer cement has recently attracted attention due to its application potential, as well as being an alternative binder with low emissions compared to conventional portland cement in concrete production. Studies intended on the mechanical properties and behaviors of structural elements produced from class C fly ash-based geopolymer concrete are important to improve the implementation. This study aimed to determine the effect of confinement on the behavior of class C fly ash-based geopolymer concrete and portland cement-based concrete. 6 specimens were made with class C fly ash-based geopolymer concrete tested under axial loading. Then, 6 specimens were made with ordinary portland cement-based concrete for comparison. The variable considered in this study is the pitch of confinement. The effect of the pitch of confinement on the enhancement strength and stress-strain of class C fly ash-based geopolymer concrete was obtained. The analytical model proposed by Richard et al. was selected to evaluate the ultimate compressive strength and ultimate compressive strain of confined geopolymer concrete in this study. The results showed that conﬁnement reinforcement improved the strength and ductility of class C fly ash-based geopolymer concrete.